POLA PERCABANGAN RANTING BAMBU APUS [Gigantochloa apus (J.A. & J.H. Schultes) Kurz.] DI ALAM - Nisyawati Saifudin (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2017)
Third nodus from branch of Gigantochloa apus were used as sampel in the making of histologic preparat. The preparat were made using parafin method with safranin-fast green dye series (Saa 1958, with modification). In the slicing phase, sampel were sliced verticaly (cross section) and horizontaly (longitudinal section). The vertical preparat were used to observe the formation of prophylls in nodus tip, meanwhile the horizontal preparat were used to observe the position of bud in nodus tip. Based on observation in vertical preparat, prophylls’ formation shows bud in amount 1,2, and 3. Meanwhile, observation in horizontal preparat shows that the second and third bud in each nodus is come from first nodus. In summary, branch complement in branch nodus of G. apus in nature is come from one primary bud that can make another bud (secondary bud). So based on that branch complement forming, we were able to know that branching pattern of G. apus is single branching.Keywords : branch complement; branching pattern; Gigantochloa apus; parafin method